Association between rotavirus gastroenteritis and intussusception: suggested evidence from a retrospective study in claims databases in the United States. Issue 1 (2nd January 2021) - Willame, Corinne; Cheuvart, Brigitte; Aris, Emmanuel; Vetter, Volker; Cohet, Catherine
ABSTRACT: The etiology of intussusception (IS), a serious gastrointestinal obstruction, remains unclear. Limited evidence suggests a role for viral infection. We investigated the risk of IS after rotavirus gastroenteritis (RV GE) in the first year of life. In this retrospective, self-controlled case series (SCCS), we assessed the risk of IS after RV GE using data from United States administrative claims databases. Incidence rate ratios (IRR) of IS were calculated for the 7- and 21-day risk periods after RV GE (main analysis) or after fracture (sensitivity analysis). A total of 290, 912, 068 subjects were screened; 42 presented claims for RV GE and IS, and 66 for fracture and IS. The IRRs of IS after RV GE were 79.6 (95% confidence interval, CI: 38.6–164.4) and 25.5 (95% CI: 13.2–49.2) in the 7- and 21-day risk periods. The sensitivity analysis showed an association between IS and fracture for both periods, suggesting potential confounding. Post-hoc analyses did not confirm the association between fracture and IS but suggested a potential association between RV GE and IS. A temporal association between RV GE and IS was detected using claims databases. Due to some limitations of the data sources, this association should be further investigated.